BIOLOGY OF THE MANGO LEAF WEBBER, ORTHAGAMANGIFERAE MISRA (LEPIDOPTERA : PYRALIDAE), A PEST ON MANGO (MANGIFERA INDICA LINN.) IN THE FRUIT BELT OF WESTERNUTTAR PRADESH - RANI, NEERA; CHATTERJEE, V. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
Orthaga mangiferae Misra (Lepidoptera : Pyralidae) had been observed by Misra, (1932), Gupta & Rai (1982). But in Western Uttar Pradesh the infestation of this leaf webber on mango trees have been recorded by Singh (1988). The maximum infestation is seen during August to November and when temperature is 32.50°C (max), 23.60°C (min.); R.H.% 91 (max.), 70 (min.); Rainfall 3.80 mm. The life cycle continues from May/June to late November. Likewise, the total duration varies from 40-45 days. The leaf webber damages the foliage and turns in to skeleton of leaf veins so badly that the production of mango is effected in the ensuing mango season causing serious damage to the orchard owners. The life cycle of the pest is significant to make effective IPM measures to suppress the pest manifestation in Saharanpur.